Influence of myristoylation, phosphorylation, and deamidation on the structural behavior of the N-terminus of the catalytic subunit of CAMP-dependent protein kinase - Tholey, Andreas; Pipkorn, Rüdiger; Bossemeyer, Dirk; Kinzel, Volker; Reed, Jennifer (Biochemistry, 2001)
A number of isoenzymes of the catalytic subunit of cAMP-dependent protein kinase arise through posttranslational modifications of the enzyme outside the catalytic domain; the biological significance of these is not yet fully clear. A clustering of sites for such modification exists at the N-terminus of the protein, where myristoylation (of Gly1), phosphorylation (at Ser10), and deamidation of Asn2 have been observed. As the first two are known to govern membrane binding and thus subcellular compartmentalization in some proteins, it was of interest to see whether the local structure of the N-terminus was being influenced by one or more of these modifications. A series of synthetic peptides mimicing the 16 N-terminal residues of the catalytic subunit Cα was produced covering the full range of possible modifications, singly and in combination, and tested for possible effects on local structure by measuring the circular dichroism under varying polarity. It was found that myristoylation and phosphorylation modify the structure in this region in opposite ways and in a manner designed to amplify the action of a potential myristoyl/electrostatic switch. To what extent deamidation of Asn2 may oppose a potential membrane binding is unknown. Deamidation, however, had no effect on the structure of the peptide either alone or in combination with acylation and/or phosphorylation, suggesting that the change of the nuclear/cytoplasmic disribution in cells caused by deamidation [Pepperkok et al. (2000) J. Cell Biol. 148, 715−726] is due to a more complex signaling mechanism. The structural implications of the data are discussed.